The Role of Peer-Assisted Learning in Enhancing Medical Students' Academic Performance: Peer-Assisted Learning in Medical Students' Academic Performance - Aman, Khaliq; Parvez, Farida; Saleem, Sadaf; Ayub, Hassan; Amin, Sarah; Salman, Ruhina (Pakistan Journal of Health Sciences, 2025)
Peer-assisted learning (PAL) has gained recognition as an innovative and interactive educational strategy in medical education. Objectives: To evaluate the impact of PAL on the academic performance and satisfaction of undergraduate medical students. Methods: A comparative quasi-experimental study was conducted at Rawal Institute of Health Sciences, Islamabad, over six months. A total of 106 students participated, including 76 who attended PAL sessions and 30 who did not. Pre- and post-tests were administered to assess academic performance. PAL sessions were conducted twice weekly for four weeks and were led by trained senior students. Student satisfaction was measured using a structured questionnaire. Data were analyzed using SPSS version 25.0. Independent-samples and paired-samples t-tests were used to assess between-group and within-group differences. A p-value of less than 0.05 was considered statistically significant. Results: Pre-test scores were similar between groups. However, PAL participants achieved significantly higher post-test scores (Mean ± SD = 73.81 ± 9.00) and greater improvement (Mean = 18.95%) compared to non-participants (Mean = 6.82%, p = 0.001). Satisfaction levels were notably high among PAL participants, with over 90% reporting an enhanced understanding, increased exam preparedness, and increased academic confidence. Conclusions: It was concluded that PAL had a positive impact on both academic performance and student satisfaction. These findings support the integration of PAL as a complementary educational approach within medical curricula.